The Role of Peroxisome Proliferator-Activated Receptor in Addiction: A Novel Drug Target - Quiroga, Carla; Barberena, Juan José; Alcaraz-Silva, Jocelyne; Machado, Sérgio; Imperatori, Claudio; Yadollahpour, Ali; Budde, Henning; Yamamoto, Tetsuya; Telles-Correia, Diogo; Murillo-Rodríguez, Eric (Current Topics in Medicinal Chemistry, 2021)
The peroxisome proliferator activated receptors (PPARs) are a superfamily of well-recognized ligand-binding nuclear receptors comprising three isoforms: PPARα, PPARγ, and PPARβ/δ. In response to endogenous lipid messengers, PPARs trigger the transcription of genes related to a wider spectrum of physiological phenomena, including fatty acid oxidation, inflammation, adipogenesis, among many others. Thus, the importance of PPARs as putative protective therapy in health issues has increased the interest of studying these nuclear receptors, including the management of neurodegenerative disorders, multiple sclerosis, and likely addiction. In recent years, several pieces of evidence from animal models have demonstrated the promising role of PPARs as a critical element for interventions in addictive behaviors by reducing the reinforcing properties of addictive substances such as alcohol. However, there is a lack of data in the scope and has so far been unexplored the function of PPARs in additional drugs such as cannabis, opioids, methamphetamine, or cocaine. A similar scenario has been found for the management of binge-type eating disorders. Thus, here we review recent advances in understanding the relevance of the PPAR controlling addiction.
Keywords: Therapy